DEVELOPMENT OF A GREEN ECONOMY IN THE REGIONS OF UZBEKISTAN - Аминов Фазлитдин Бахадирович (American Journals, 2026)
The article analyzes the theoretical foundations and practical features of the development of the regional economy based on the principles of the "green" economy. The influence of such factors as environmental sustainability, rational use of natural resources, the introduction of alternative energy sources on the socio-economic development of the regions is considered.
Keywords: Green economy, environmental sustainability, regional development, alternative energy, environmental innovations, organic farming, clean technologies, waste-free production, resource circulation.